1984
DOI: 10.1002/jmv.1890130303
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutination by human rotavirus strains

Abstract: Human rotavirus isolates, KUN , MO, and Wa strains were found to agglutinate erythrocytes of the day-old chicken and adult goose, optimally at pH 6.6. Only those fractions containing double-shelled rotavirus particles isolated by isopycnic centrifugation in cesium chloride had hemagglutinating activity. Trypsin treatment decreased the hemagglutination titer of human rotavirus strains and conversely increased their infectivity. Hemagglutination inhibition tests with antisera against type-specific antigens demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…The virus supernatants were stored at -80 °C until use. The virus stock titers were 5 x 105 fluorescent cell forming units (fefu) per ml [4] with HP~V and 1 × t0 s TCIDs0 per ml with VSV, respectively.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus supernatants were stored at -80 °C until use. The virus stock titers were 5 x 105 fluorescent cell forming units (fefu) per ml [4] with HP~V and 1 × t0 s TCIDs0 per ml with VSV, respectively.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The KUN strain of HRV (serotype 2, subgroup 1) [7] and the Indiana strain of VSV were used. Infectious HRV was grown in MEM without serum and containing 0.5 gg/ml of trypsin (Sigma type V-S) for 24 hours [4], VSV was grown in MEM without serum for 24 hours. The cultures were freeze-thawed two times and cell debris was removed by low-speed centrifugation.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…We have also shown biological effects of trypsin on human rotaviruses (Kitaoka et al 1984;Kitaoka et al 1986 b). In this context, it is of interest to note that trypsin-enhanced plaque formation and growth restriction of the fastidious viruses in tissue culture have been shown to be a function of the 4th gene segment by genetic analysis of cultivable reassortants between a cultivable bovine rotavirus and noncultivable human rotaviruses (Kalica et al 1983).…”
Section: Discussionmentioning
confidence: 92%
“…Our previous studies revealed that human rotavirus isolates including the KUN strain are activated in infectivity by trypsin treatment, while their hemagglutination activity is decreased (Kitaoka et al 1984; Kitaoka et al 1986 b). It has also been demonstrated that the monoclonal antibodies against HA of the KUN strain react only with Vp4 and its smaller trypsin cleavage products P30 and P24 (Kitaoka et al 1986 a).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation